PEMBERDAYAAN UMKM MELALUI PENERAPAN TEKNOLOGI INFORMASI PADA MASA PANDEMI COVID-19 DI DESA ADAT KAPAL KECAMATAN MENGWI KABUPATEN BADUNG - Ni Putu Trisna Windika Pratiwi (UNHI Press, 2021)
The village economy can be a measure of the progress of an area. MSMEs have an important and strategic role in national economic development. Information technology is considered to be able to increase business productivity, especially during a pandemic like now, where all people's activities are still limited. MSMEs located in the Traditional Ship Village consist of various kinds of businesses such as pottery, clay crafts, building materials and ceremonial materials. These MSMEs produce quality products and are quite well known. The implementation of this Community Service Activity (PKM) is located in the Traditional Ship Village which is included in the Mengwi District, Badung Regency, Bali Province. This activity targets MSME owners in the surrounding area, as users of information technology and drivers of village economic activities. The community partnership program that has taken place from the process of socialization, discussion, training and mentoring has been as expected. As a strategy to improve the abilities and skills of MSME owners, apart from socialization media, it is also carried out by providing information technology-based training, and assistance to strengthen the understanding of MSME owners so that they are able to develop their business independently and encourage the economy of Traditional Ship Villages in particular and in Bali in general.